2004
DOI: 10.1063/1.1630956
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic interactions in calcium and sodium ladder vanadates

Abstract: Magnetic interactions in ladder vanadates are determined with quantum chemical computational schemes using the embedded cluster model approach to represent the material. The available experimental data for calcium vanadate is accurately reproduced and the nature of the interladder interaction is established to be ferromagnetic. An analysis of the main contributions to the magnetic couplings is presented and the role of the covalently bonded apex oxygen is elucidated. In the sodium vanadate, the ground state co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 82%
See 1 more Smart Citation
“…Many calculations have shown the performance of DDCI estimates of the magnetic coupling. [20][21][22][23][24][25][26][27][28][29][30][31][32] The results reported in Table I show that the J values obtained at CAS+ S and DDCI2 levels are far from experimental ones, which suggest that an important part of the effects is missed. It is therefore concluded that 2h-1p and 1h-2p configurations bring from 30% to 50% of magnetic coupling.…”
Section: ͑8͒mentioning
confidence: 82%
“…So far, the DDCI approach has been extensively employed in the evaluation of J in molecular and solid state magnetic materials with a remarkable good agreement with experiment. [20][21][22][23][24][25][26][27][28][29][30][31][32] Some years ago we took benefit of this methodology to analyze in depth the physical contributions to the magnetic coupling on a series of binuclear Cu ͑II͒ complexes. 33 The use of the DDCI strategy allows not only to obtain quite accurate J values but also to analyze the various physical effects by generating CI spaces of increasing lengths that include different types of determinants.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure makes use of the effective Hamiltonian theory, and it has been previously used in the study of magnetic systems, as well as the evaluation of hopping integrals in mixed-valence systems. [29][30][31][32][33][34][35][36][37][38][39][40][41] A detailed description of the method can be found in Ref. 41, and a summary enlightening the most striking points will be provided here.…”
Section: ͑4͒mentioning
confidence: 99%
“…This strategy has been extensively used in the recent past, especially in the evaluation of magnetic coupling constants as well as the determination of hopping integrals in numerous systems. [29][30][31][32][33][34][35][36][37][38][39][40][41]46,48,49,61,62 The whole procedure can be summarized as follows. ͑1͒ A fragment of the bulk structure of TiO 2 has been chosen, containing two neighbor Ti centers, and the ten oxygen atoms around them, as shown in Fig.…”
Section: Approximation To the Exact N-electron Wave Functionsmentioning
confidence: 99%
“…Furthermore, there exists by now substantial evidence in the literature that the electronic structure parameters considered here do not critically depend on the value of the charges to calculate the Madelung potential. [22][23][24] This observation only holds for ionic transition metal compounds. In case of materials with covalent bonds such as CuGeO 3 , the embedding procedure with formal charges does not lead to meaningful results and alternative embedding schemes should be applied.…”
Section: Computational Informationmentioning
confidence: 99%